Risk Factors of Depressive Symptoms among Community-Dwelling Elderly - Eunhee Lee (International Journal of Advanced Culture Technology(IJACT), 2018)
The purpose of this study was to assess risk indicators of depressive symptoms such as demographic, socio-economical domains (age, gender, marital status, education, child, religion, income, health, friendship) and personality domains (neurotic personality, self-esteem and life goal attitude) of community dwelling elderly persons. A total of 300 community-residing elderly participants aged 65+ in a metropolitan city in Korea, were recruited for this interview survey. The interview covered demographic and socio-economic characteristics, and administration of the 20-item Korean Version of CES-D, the 10-item Self-esteem, the 19-item Neuroticism and the 10-itm Goal Instability scale. The prevalence of significant depressive symptoms (CES-D scale >= 21) was 31%. Logistic regression analysis showed high risk for depression was associated with high neuroticism, less intimate friendship, high goa1 instability, and childlessness, respectively in the order of significance. Factors in the personality domains were more strongly associated with depressive symptoms than factors in the socio- economical domains. Both cultural and universal meaning of the findings was discussed with regard to intervention.